Confirmation of the presence of Janicea antiguensis (Chace, 1972) (Decapoda: Barbouriidae) in northeastern and eastern Brazil - Giraldes,Bruno W. (2012)
The barbouriid shrimp Janicea antiguesis (Chace, 1972) is reported from Porto de Galinhas and Tamandaré in Pernambuco and Guarapari in Espírito Santo, Brazil. These records confirm the presence of J. antiguensis in northeastern and eastern Brazil, considerably extending its Brazilian range from Fernando de Noronha to southern Espírito Santo and also representing the first record of this species from mainland coastal reefs. In Brazil, J. antiguensis occurs in or near marine reef caves, typically at depths between 5 and 15 m, and can be most easily observed while scuba diving at night. Colour photographs of J. antiguensis from various Atlantic localities are provided and its colour pattern is compared to that of the closely related Indo-West Pacific barbouriid shrimp, Parhippolyte misticia (Clark, 1989). Some in situ observations are provided for the Porto de Galinhas population of J. antiguensis. Multiple observations of pairs with both individuals brooding embryos at different developmental stages suggest protandric simultaneous hermaphroditism in J. antiguensis.